COMPANY LIABILITY FOR DEFAULT IN THE EVENT OF PACKAGES NOT ARRIVING AT THE ADDRESS BY COURIERS: A COMPILATION OF SHARIA ECONOMIC LAW PERSPECTIVE - Utami Riska Nita; Abd. Rahman Harahap (Journal Analytica Islamica, 2025)
This study examines the liability of delivery service companies for breach of contract in the form of undelivered packages to the intended address, from the perspective of the Compilation of Sharia Economic Law (Kompilasi Hukum Ekonomi Syariah/KHES), using a case study in Sei Litur Tasik Village, Sawit Seberang Subdistrict, Langkat Regency. The background of the research stems from increasing public complaints regarding delivery services failing to fulfill their obligations as agreed. The purpose of this study is to analyze the implementation of package delivery by the company, identify the factorx contributing to undelivered packages, examine the forms of corporate accountability for delivery failures, and assess such accountability according to the Compilation of Sharia Economic Lave. This research employs an empirical juridical method with a conceptual and statutory approach. Data were obtained through interviews, field observations, and document analysis. The findings indicate that, based on Chapter III Article 36 of KHES concerning breach of contract and Chapter IV Article 85 regarding the handover of goods as stated in the shipping receipt, the main causes of breach were courier negligence, data system errors, and weak internal supervision. According to Chapter III Article 38 of KIES, the forms of liability provided by the company typically involve compensation in the form of a shipping cost refund or package redelivery; however, these measures are often insufficient and lack transparency. From the perspective of the Compilation of Sharia Economic Law, such a breach violates the ijarah (service lease) contract and obliges the company to provide fair and accountable compensation. The conclusion of this research emphasizes the importance of applying Sharia principles in service-based businesses to uphold consumer rights and achieve justice